Investigating accessibility issues of UI mobile design patterns in online communities: a virtual ethnographic study - Casadei, Vitor Casadei; Granollers, Toni Granollers; Zaina, Luciana Zaina (Teste, 2019)
With the dissemination of mobile devices and the migration of activities that were once executed only on desktop computers to smartphones and tablets, the concerns related to accessibility in this environments have increased. However, the accessibility impact of mobile interface design patterns in the life of disabled people has not been widely addressed in academic works. At the same time, the community of mobile designers and developers has made significant advances in identifying accessibility issues with design patterns on mobile interfaces, reporting these findings in virtual spaces of discussions as forums, blogs, etc. Aiming at exploring the experiences and knowledge of professionals, this paper presents an ethnography study in 18 virtual communities of mobile design and development with the goal of identifying issues on the accessibility of Android mobile UI design patterns. As a result, we analyzed 127 documents in order to propose recommendations to improve the accessibility of mobile interfaces.